2021
DOI: 10.3390/jcm10040723
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Periodontal Inflamed Surface Area by Simple Oral Examination

Abstract: The periodontal inflamed surface area (PISA) is a useful index for clinical and epidemiological assessments, since it can represent the inflammation status of patients in one contentious variable. However, calculation of the PISA is difficult, requiring six point probing depth measurements with or without bleeding on probing on 28 teeth, followed by data input in a calculation program. More simple methods are essential for screening periodontal disease or in epidemiological studies. In this study, we tried to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Periodontal disease, initiated by bacterial biofilms, can cause the destruction of soft and hard periodontal tissues, consequently leading to tooth loss [ 5 , 6 , 7 ]. Periodontal disease produces inflammatory mediators and microbial products that can enter the systemic circulation through the mouth and reach distant organs [ 8 , 9 ]. Indeed, several studies have shown a link between periodontal disease and some frequent systemic pathologies [ 10 ] such as diabetes [ 11 ], cardiovascular disease [ 12 , 13 ], respiratory disease [ 14 ], obesity [ 15 ], cancer [ 16 , 17 ], and preterm birth (PTB) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal disease, initiated by bacterial biofilms, can cause the destruction of soft and hard periodontal tissues, consequently leading to tooth loss [ 5 , 6 , 7 ]. Periodontal disease produces inflammatory mediators and microbial products that can enter the systemic circulation through the mouth and reach distant organs [ 8 , 9 ]. Indeed, several studies have shown a link between periodontal disease and some frequent systemic pathologies [ 10 ] such as diabetes [ 11 ], cardiovascular disease [ 12 , 13 ], respiratory disease [ 14 ], obesity [ 15 ], cancer [ 16 , 17 ], and preterm birth (PTB) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of inflamed tissues was estimated using standard clinical parameters for periodontal disease, including blood on probing (BOP), clinical attachment level (CAL), PD, and plaque index. 27 Both diseases exhibited significant inflammation compared with healthy tissues; however, no substantial differences were observed between periodontitis and periimplantitis (Table 1). Although some immune cells demonstrated marked elevations in value, most immune cell subtypes exhibited similar abundance patterns between cases, (see Figure S1 in online Journal of Periodontology).…”
Section: Discussionmentioning
confidence: 95%
“…This genetic heterogeneity may be attributed to biological factors such as local inflammatory differences or distinct immunological profiles. The severity of inflamed tissues was estimated using standard clinical parameters for periodontal disease, including blood on probing (BOP), clinical attachment level (CAL), PD, and plaque index 27 . Both diseases exhibited significant inflammation compared with healthy tissues; however, no substantial differences were observed between periodontitis and peri‐implantitis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vitamin D’s positive effects in immune regulation might have not only a positive role in oral health management and bone health, but also in the downregulation of inflammatory mediators that promote tumor growth or risk of recurrence [ 61 , 62 ]. Concurrently, periodontitis and gingivitis have been related to increases in immune response and systemic inflammation [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%